2010
DOI: 10.2108/zsj.27.851
|View full text |Cite
|
Sign up to set email alerts
|

The Introduced Asian Parasitic CopepodNeoergasilus japonicus(Harada) (Cyclopoida: Ergasilidae) from Endangered Cichlid Teleosts in Mexico

Abstract: The cyclopoid copepod Neoergasilus japonicus ( Harada, 1930 ) is recorded from three endangered or threatened fish species from southeast Mexico: the tailbar cichlid Vieja hartwegi (Taylor and Miller, 1980); the Angostura cichlid V. breidohri (Werner and Stawikowski, 1987); and the sieve cichlid C. grammodes (Taylor and Miller, 1980). This ectoparasitic copepod is considered, together with most other members of Neoergasilus, an Eastern Asian form. N. japonicus is one of the most widespread parasitic Asian cope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
2
10
0
5
Order By: Relevance
“…As was expected by Suárez-Morales et al (2010), this parasite is advancing to other areas of the Neotropical region. In the present study, we report the occurrence of N. japonicus in Colossoma macropomum (Cuvier, 1818) for the first time in South America, more specifically in the Peruvian Amazon.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…As was expected by Suárez-Morales et al (2010), this parasite is advancing to other areas of the Neotropical region. In the present study, we report the occurrence of N. japonicus in Colossoma macropomum (Cuvier, 1818) for the first time in South America, more specifically in the Peruvian Amazon.…”
Section: Introductionsupporting
confidence: 67%
“…Although it is an originally described from Asia, N. japonicus has been also recorded in Hungary (Ponyi and Molnar 1969), Czechoslovakia (Hanek 1968), Britain (Mugridge et al1982), France (Lescher-Moutoué 1979), Finland (Tuuha et al 1992), Italy (Alfonso and Belmonte 2010), Russia (Dogiel andAkhmerov 1952, Gussev andSmirnova 1964), India (Kumari et al 1988), Iran (Mirzaei and Khovand 2015), in North America for the first time in 1993 from aquaculture ponds at Auburn University in Alabama (Hayden and Rogers 1998), Cuba (Prieto 1985), Mexico (Suárez-Morales et al 2010;Suárez-Morales et al 2013). Until the present, it has never been registered in South America.…”
Section: Introductionmentioning
confidence: 99%
“…The higher proportion of adult stages (11) and autogenic species (12) suggests that these cichlids play an important role as defini-tive hosts for most helminth taxa in the upper GRB and that these metazoans mature within the aquatic environment. Occurrence of Schyzocotyle acheilognathi (Yamaguti, 1934) in the three cichlids represent new host records for this Asiatic parasite that was introduced into Mexico along with carp (Cyprinus carpio Linnaeus, 1758) (Salgado-Maldonado & Pineda-López, 2003;Suárez-Morales et al, 2010). Neoergasilus japonicus (also co-introduced along with C. carpio) has been recently reported from the same hosts/sites from the upper GRB (see Suárez-Morales et al, 2010), while S. acheilognathi has already been recorded in all Mexican states (with exception of Baja California) (Salgado-Maldonado & Rubio-Godoy, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the N. japonicus infestation in ornamental fish and the studies performed in different parts of the world, it can be concluded that N. japonicus can simply cause changes in hosts living in fresh water systems. Moreover, the copepod can infest a broad spectrum of fish even in geographically limited areas and also can use both the native and nonnative fish as the host, and this capability is one of the reasons of its spread all over the world (Kim and Choi 2003;El-Rashidy and Boxshall 2009;Suarez-Morales et al 2010;Nagasawa and Inoue 2012). All the removed copepods in this study were female because adult males and larva live freely, and only females are parasitic (Kabata 1979).…”
Section: Discussionmentioning
confidence: 99%